2020
DOI: 10.1016/j.redox.2020.101750
|View full text |Cite
|
Sign up to set email alerts
|

Loss of USF2 promotes proliferation, migration and mitophagy in a redox-dependent manner

Abstract: The upstream stimulatory factor 2 (USF2) is a transcription factor implicated in several cellular processes and among them, tumor development seems to stand out. However, the data with respect to the role of USF2 in tumor development are conflicting suggesting that it acts either as tumor promoter or suppressor. Here we show that absence of USF2 promotes proliferation and migration. Thereby, we reveal a previously unknown function of USF2 in mitochondrial homeostasis. Mechanistically, we demonstrate that defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…We focused our experimental validation on one such modifier, the transcription factor USF2. By tracing USF2’s function in proliferation and genome-wide expression in untreated cells, we extended conclusions from studies of USF2 in tumor suppression and cell cycle regulation (Qyang et al 1999; Pawar et al 2004; Chen et al 2006; Hu et al 2020), apoptosis (Sato et al 2011) and ERK1/2 signaling (Chi et al 2020). In an acute DNA damage setting, we discovered that USF2 is required for cells to mount DNA repair and downstream DNA damage responses.…”
Section: Discussionmentioning
confidence: 62%
“…We focused our experimental validation on one such modifier, the transcription factor USF2. By tracing USF2’s function in proliferation and genome-wide expression in untreated cells, we extended conclusions from studies of USF2 in tumor suppression and cell cycle regulation (Qyang et al 1999; Pawar et al 2004; Chen et al 2006; Hu et al 2020), apoptosis (Sato et al 2011) and ERK1/2 signaling (Chi et al 2020). In an acute DNA damage setting, we discovered that USF2 is required for cells to mount DNA repair and downstream DNA damage responses.…”
Section: Discussionmentioning
confidence: 62%
“…The upstream stimulatory factors (USFs) USF1 and USF2 all belong to the helix-loop-helix leucine zipper transcription factor family and function as homodimers or heterodimers by binding to the e-box of the target DNA core sequence (5′-CANNTG-3′) [ 30 , 31 ]. USFs play an important role in stress, the immune response, energy metabolism, and cell development [ 32 34 ]. The role of USF2 seems to be more critical than that of USF1 [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to ROS, transcription factors can affect pyroptosis by regulating its associated molecules. For example, upstream stimulatory factor 2 (USF2), which is a member of the basic helix-loophelix-leucine zipper transcription factor family, can regulate a variety of cellular processes (Sirito et al, 1992;Chi et al, 2020). In SAKI, Sun et al found that the knockdown of USF2 led to the inhibition of the TGF-b/suppressor of mothers against d e c a p e n t a p l e g i c ( S m a d ) 3 s i g n a l i n g p a t h w a y b y downregulating the expression of thrombospondin1 (THBS1), thereby reducing pyroptosis and improving renal injury (Sun et al, 2022).…”
Section: Regulation Of Pyroptosis By Transcription Factorsmentioning
confidence: 99%